School, family and the community in cooperation: the model of syneducation - Mylonakou, Iro; Kekes, Ioannis (International Journal about Parents in Education, 2023)
School, family and the community constitute three distinct but at the same time interdependent systems.  The ideas, notions and research which are related to the necessity of the functional communication of those systems have recently flourished internationally, creating a substantial “heritage” in principles, acceptances, theoretical models, application proposals, research programs as well as new orientations and perspectives.  This paper proposes the model of syneducation.  As syneducation (synergy + education) we define the acquisition of a common educational experience, simultaneously and in cooperation, of persons differing in age and cognitive infrastructure and often in social and cultural level. Syneducation is a new emerging research field.  With its application, we aim at the change of attitudes and behaviours of the participants (parents, educators, students, policy makers and the representatives of the community) from an initial state of possible indifference- disinterest to an active and effective participation in common syneducational actions in order to face specific issues, and even further to being multipliers of the above mentioned actions. Furthermore, the application of this model creates, develops and accrues social capital.In this paper we will present certain research applications which took place according to the model of syneducation based on the methodology of collaborative action research (for example, a transdisciplinary research program, a research program in Literacy in Information Technology, a research program focusing on problem management within the family etc.) The research findings and the prospects of the syneducation model are still being discussed. This model is proposed as a realistic way of thought and action adapted to the contemporary conditions of our technological era and the foreseen needs of social computing.